Implementation CIPP Evaluation of Keaksaraan Usaha Mandiri Program - Heryahya, Andang; Sujanto, Bedjo; Rugayah, Rugayah (Universitas Negeri Semarang, 2020)
The number of illiterate populations in 2019 aged 15-59 years was 3,474,694 people spread throughout the Regency/City in Indonesia. Since 2005 the government has published an independent business literacy program as part of efforts to eradicate illiteracy, poverty and ignorance. This study aims to determine the implementation of the program with the CIPP evaluation model. Using a qualitative approach with a case study method in six community education institutions in five sub-districts in Bogor Regency. Data obtained through interviews, observation and documentation. The results showed that the Kekasaraan Usaha Mandiri program was carried out in a dense, illiterate environment in rural and mountainous areas. The main cause of illiteracy is the low economic income of the family which has an impact on dropping out of school and a short way of thinking of the community, with the perception that the most important thing is to be able to make money even though you have to be a manual worker. Organizers have an understanding of the literacy education development as part of efforts to educate the nation’s life. Educational literacy in the implementation of learning using product packaging and marketing materials that are not delivered optimally because the competency and entrepreneurial experience of the teacher is insufficient. Learning innovations that can integrate literacy education, business activities and religious education need to be done. Then it is necessary to improve entrepreneurship competencies for tutors, as well as collaborating with microfinance institutions or local entrepreneurs.